2017
DOI: 10.1002/elan.201700426
|View full text |Cite
|
Sign up to set email alerts
|

Fullerene Black Modified Screen Printed Electrodes for the Quantification of Acetaminophen and Guanine

Abstract: Fullerene Black (FB) and Extracted Fullerene Black (EFB) were used in modified screen‐printed electrodes producing electrochemical transducers (FB‐SPEs and EFB‐SPEs). A complete electrochemical study was performed and the best results are obtained working with FB‐SPEs, especially in terms of: 1. improved electron‐transfer kinetic mechanisms and 2. sensitivity and selectivity toward Acetaminophen (Ac) and Guanine (G). These latter represent two important electro‐active targets to quantify in medicine field appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…This family is composed essentially of Gr, CNTs, CQDs and fullerene. Table 2 [ [17] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ] summarizes types of electrodes, modifiers, analytical figures of merits, and the advantages/disadvantages of each modifier used for PCT determination.…”
Section: Carbon-based Nanomaterials Modified Electrodes For Pct Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…This family is composed essentially of Gr, CNTs, CQDs and fullerene. Table 2 [ [17] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] ] summarizes types of electrodes, modifiers, analytical figures of merits, and the advantages/disadvantages of each modifier used for PCT determination.…”
Section: Carbon-based Nanomaterials Modified Electrodes For Pct Determinationmentioning
confidence: 99%
“…Valentini et al. [ 45 ] used fullerene black for the modification of SPCEs to determine PCT and guanine in urine and pharmaceutical formulations samples. The fullerene black was obtained under the form of carbon soot by arcing graphite in a helium atmosphere, and then coated on the surface of SPCE through drop-casting.…”
Section: Carbon-based Nanomaterials Modified Electrodes For Pct Determinationmentioning
confidence: 99%
“…The electric arch method is considered the most efficient in producing large amounts of fullerene. Some interesting research studies have shown that black fullerene has a good electrochemical activity for acetaminophen and guanine [16,144]. In a recent work, a sensitive SPCE electrochemical sensor based on palladium nanoparticles (PdNPs) decorated fullerene (C60) for dopamine was reported [145].…”
Section: Fullerene-modified Electrodesmentioning
confidence: 99%
“…According to the authors, the designed biosensor has great potential to detect ATP at ultralow levels (detection limit of 3.30 fM). Recent works have shown the design of sensors for L-histidine [32], prostate antigen [151], proteins [152,153], biomarkers [154,155], and several others biomolecules [156][157][158][159].…”
Section: Great Response Formentioning
confidence: 99%